Gambaran Perundungan (Bullying) Pada Siswa SMK Kesehatan Triple J Citeureup Jawa Barat - Ariffandi, Muhammad Raihan; Sofiana, Sofiana (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
This research focuses on the description of bullying cases that occur among students of SMK Kesehatan Triple J Citeureup, West Java. Bullying is an aggressive action that is unwanted by the victim, either an individual or a group. This action is carried out with the aim of hurting the victim, both physically and emotionally. Bullying recurs or has the potential to recur in the future. The research method used was descriptive quantitative using the Olweus Bully/Victim Questionnaire (OBVQ) to measure three types of bullying, namely verbal, physical, and non-verbal/non-physical. The research sample consisted of 88 students selected by total sampling. The study showed verbal bullying was the most frequent form of bullying, with 43.2% of students reporting never experiencing verbal bullying, 42% experiencing bullying once or twice a month, and 14.8% experiencing bullying one or more times a week. Physical bullying was reported by 69.3% of students who never experienced it, 22.7% experienced physical bullying once or twice a month, and 8% experienced physical bullying one or more times a week. Meanwhile, non-verbal/non-physical bullying was reported by 53.4% of students who had never experienced it, 28.4% experienced bullying once or twice a month, and 18.2% experienced bullying one or more times a week. This shows that bullying is still a serious problem in the school environment, especially verbal bullying. This study calls for a comprehensive intervention program to reduce bullying, including education on the impact of bullying, psychological support for victims, and the development of social skills among students. In addition, it is important for schools to develop clear anti-bullying policies and involve all parties, including teachers, parents, and students, in an effort to create a safe and inclusive school environment.